Stage art: a model of reality as a semiotic system - Shumakova, Svitlana (My University, 2023)
The article interprets the artistic essence of stage art, which predetermines a certain duality - modeling and sign, obeying the laws of semiotic systems. Stage art in this aspect is considered in connection with such concepts as "sign". The conclusion is formulated: the plan of content and the plan of expression in the sign system of a stage work against the background of a certain aesthetic expectation become a semantically saturated meaning-bearing construct, equal to a verbal expression that receives new, additional meanings.
Keywords: сценічне мистецтво, performing arts